Mini-plate versus Reconstruction Plate: A Comparative Analysis of Complications in Free Fibula Osteocutaneous Flaps for Oral Cancer - Rithin George; Sandeep Vijay; Anoop Attakkil; Raveena Nair; Linu Thomas; Aswin Mullath (Journal of Head & Neck Physicians and Surgeons)
Background: Advanced Oral cancers require segmental mandibulectomy, which ideally requires fibula flap reconstruction. Mini-plates or reconstruction plates are used for fibula fixation as per the surgeon’s preference, but the complication rates of each have hardly been studied. The purpose of this study was to find the incidence of plate-related complications, the factors attributing to it, and the difference in complication rates between mini-plate and reconstruction plate for fibula flap fixation exclusively in oral cancer patients who underwent segmental mandibulectomy as part of ablative surgery. Materials and Methods: The study was a retrospective observational study of oral cancer patients who underwent free fibula osteocutaneous flap reconstruction for mandibulectomy defects from November 2010 to November 2020 at a tertiary cancer center in India. Statistical Methods: Chi-square test, Fisher’s exact test. Results: Thirty-nine patients were included in the study and the mean follow-up period was 31 months. Seventeen of them had mini-plate fixation, 16 had reconstruction plate fixation and in two patients, both were used. About 25.64% of patients had complications. In the mini-plate group, 11.7% of patients had complications whereas 44.4% had complications in the recon plate group. 9/32 patients who took adjuvant treatment had complications, and in this subset of patients, there was a significant difference in the incidence of complications between the mini and recon plate groups (P = 0.03). Conclusion: Mini-plates are associated with less complications while used for fixation in microvascular fibula osteocutaneous flaps in oral cavity malignancy who are potential candidates for adjuvant treatment.